Vaginal Microbiota, Genital Inflammation and Extracellular Matrix Remodelling Collagenase: MMP-9 in Pregnant Women With HIV, a Potential Preterm Birth Mechanism Warranting Further Exploration - Short, Charlotte-Eve S.; Quinlan, Rachael A.; Wang, Xuan; Preda, Veronica Georgiana; Smith, Ann; Marchesi, Julian R.; Lee, Yooni S.; MacIntyre, David A.; Bennett, Phillip R.; Taylor, Graham P. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Pregnant women living with HIV-infection(PWLWH) have elevated rates of preterm birth(PTB) in which HIV and combination-antiretroviral-therapy(cART) are implicated. PWLWH also have a high prevalence of adverse vaginal microbiota, which associate with genital-tract inflammation. The mechanism underlying PTB in PWLWH is unknown. We present the first data in PWLWH on genital-tract matrix-metalloproteinase-9(MMP-9), an important collagenase implicated in labour onset, and tissue-inhibitor-of-metalloproteinases-1(TIMP-1) and explore correlations with local inflammation and vaginal bacteria. Material and Methods: Cervical-vaginal fluid(CVF) collected by a soft cup and high vaginal swabs(HVS) were obtained from PWLWH and HIV uninfected pregnant women(HUPW) at three antenatal time-points. Maternal characteristics, cART exposure, and pregnancy outcome were recorded. Concentrations of MMP-9, TIMP-1 and ten cytokines were measured by immunoassays. Vaginal microbiota composition was determined through 16S rRNA-amplicon sequencing. MMP-9, TIMP-1 and cytokine concentrations were compared by HIV-status, cART, and prematurity and in PWLWH correlations with polymorphonuclear leucocytes, cytokines and bacterial genera were explored. Results: CVF was available for 50 PWLWH(108 samples) and 12 HUPW(20 samples) between gestation weeks 14-38. Thirty-six PWLWH conceived on cART and 14 initiated post-conception. There were five and one PTB outcomes in PWLWH and HUPW respectively. PWLWH had higher mean CVF concentrations of MMP-9(p<0.001) and TIMP-1(p=0.035) in the second trimester compared with HUPW with a similar trend in the third trimester. PWLWH also had higher CVF values of cytokines: IL-1alpha, IL-8, IL-12 and TNF-beta in both trimesters compared to HUPW (p≤0.003). In PWLWH, MMP-9 positively correlated with TIMP-1(r=0.31, p=0.002) and CVF polymorphonuclear leucocytes(r=0.57, p=0.02). Correlations were observed between MMP-9 and three cytokines: IL-1beta(r=0.61), IL-8(r=0.57) and TNF-alpha(r=0.64), p<0.001, similarly for TIMP-1. Abundance of anaerobic pathobionts correlated with MMP-9: Gardnerella(r=0.44, p<0.001), Atopobium(r=0.33, p=0.005), and Prevotella genera(r=0.39, p<0.001). Conversely proportion of Lactobacillus genera negatively correlated with MMP-9(rho=-0.46, p<0.001). MMP-9/TIMP-1 ratio increased with gestational age at sampling in PWLWH, but this was no longer significant after adjusting for confounders and no difference by prematurity was observed in this sub-study. Conclusions: Here we show strong correlations of MMP-9 to genital-tract inflammation and sub-optimal bacterial genera in PWLWH indicating the ascending genital-tract infection pathway may be a contributory mechanism to the high-risk of PTB.